Evaluación preliminar de los niveles de partículas atmosféricas PM10 y PM2,5 en la ciudad de Maracaibo, Venezuela. - Morales, José; Cano, Yulixis; Sánchez, Ligbel; Torres, Julio; Stanislao, Irene; Montilla, Brinolfo (Multiciencias)
Ver resumen pdf.